In memory of Nikolai Vasilievich Putov (on the 100th anniversary of his birth) - A. L. Akopov; N. Yu. Kokhanenko (Вестник хирургии имени И.И. Грекова)
In 1923, the outstanding doctor, scientist and teacher, corresponding member of the Russian Academy of Medical Sciences, Professor Nikolai Vasilyevich Putov, turns 100 years old. Under his leadership, the Research Institute of Pulmonology successfully served as the country’s leading institution on the relevant problem and became one of the leading medical research centers in the Soviet Union. Headed by him Department of Hospital Surgery ¹ 1 of the First Leningrad Medical Institute named after Academician I. P. Pavlov was a leader in university and postgraduate teaching of surgery and surgical science. N. V. Putov was the extraordinary teacher, he had the excellent understanding of issues of universal human culture. He was known and appreciated, people were proud of the friendship with him not only in Leningrad – St. Petersburg, but also in Russia and abroad.